1998
DOI: 10.1038/sj.onc.1202113
|View full text |Cite
|
Sign up to set email alerts
|

Induced p53 expression in lung cancer cell line promotes cell senescence and differentially modifies the cytotoxicity of anti-cancer drugs

Abstract: The p53-null human lung cancer cell line H1299 was used in order to generate clones with ecdysone-inducible p53 as well as ecdysone-inducible p21 waf1 . Induced expression of p53 resulted in irreversible cell growth arrest with characteristics of replicative senescence, suggesting that p53 can prevent immortalization by activating a senescence program. The eect of induced p53 and p21 waf1 expression on the cytotoxic action of the anti-cancer drugs etoposide and cisplatin was also analysed. Whereas p21 waf1 ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 27 publications
3
66
0
3
Order By: Relevance
“…The induction of senescence by p21 waf takes 4 ± 6 days ( Figure 4) and results in loss of colony formation capability. Previous work on overexpression of p53 in the EJ cell line and our results on overexpression of p53 in H1299 cells (Wang et al, 1998) also demonstrated that the p53-dependent growth arrest resulted in senescence (Sugrue et al, 1997). This raised the possibility that senescence may be an important mechanism which prevents tumorigenesis and may be an alternative to apoptosis.…”
Section: Discussionsupporting
confidence: 71%
“…The induction of senescence by p21 waf takes 4 ± 6 days ( Figure 4) and results in loss of colony formation capability. Previous work on overexpression of p53 in the EJ cell line and our results on overexpression of p53 in H1299 cells (Wang et al, 1998) also demonstrated that the p53-dependent growth arrest resulted in senescence (Sugrue et al, 1997). This raised the possibility that senescence may be an important mechanism which prevents tumorigenesis and may be an alternative to apoptosis.…”
Section: Discussionsupporting
confidence: 71%
“…The induction of a senescent-like phenotype has also been demonstrated in tumour-derived cell lines. In particular, activation of a senescence programme in neoplastic cells has been obtained either by reintroduction of critical regulators of replicative senescence [25,37] or by treatment with anti-cancer agents [42]. Most interestingly, expression of several CKI, in both normal and tumour cells [23,24], triggers premature senescence.…”
Section: Induction Of a Senescent-like Phenotypementioning
confidence: 99%
“…Cell lines derived from tumours are generally capable of extended proliferation: indeed, limitless replicative potential represents one of the de novo acquired capabilities of tumour cells, and the ability to repress senescence pathways appears to contribute to tumorigenesis [22]. Accordingly, restoration of senescence regulatory pathways in tumour cells rapidly elicits senescence [23][24][25]. These observations suggest that, in several immortal tumour-derived cell lines, the genetic programme of senescence is repressed, but not lost, in such a way that it can be reactivated by expression of critical regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Although cancer cells bypass both replicative and oncogene-induced senescence, the genetic program of senescence in these cells seems to be repressed, but not lost, in such a way that it can be reactivated by expression of critical regulators. Accordingly, restoration of senescence regulatory pathways in tumor cells rapidly elicits senescence (Wang et al, 1998(Wang et al, , 1999. In addition, a process termed stress-induced or premature senescence can be readily elicited in tumor cells by treatment with sublethal concentrations of conventional anticancer drugs (Chang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%